2022
DOI: 10.1089/tmj.2021.0200
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Patient Satisfaction with Live-Interactive Teledermatology Visits During the COVID-19 Pandemic: A Survey Study

Abstract: Background: Coronavirus disease 2019 has brought teledermatology to the forefront. Understanding patients' experiences will clarify its benefits and limitations. Materials/Methods: Patients evaluated through live-interactive teledermatology at New York University Langone Health March-June 2020 were surveyed. Patient demographics, satisfaction with, and preferences between teledermatology and in-person visits across four domains (visit preparation, provider communication, physical examination, and treatment pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…It reduces waiting times and costs, improves access in rural areas and/or for patients who experience difficulties in attending in-person appointments and decreases appointment cancellations and absenteeism. Moreover, TD proves to be a useful diagnostic and follow-up tool, favoring early referral in emergency cases [ 11 , 13 , 14 ]. There are, however, other aspects that adversely affect TD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It reduces waiting times and costs, improves access in rural areas and/or for patients who experience difficulties in attending in-person appointments and decreases appointment cancellations and absenteeism. Moreover, TD proves to be a useful diagnostic and follow-up tool, favoring early referral in emergency cases [ 11 , 13 , 14 ]. There are, however, other aspects that adversely affect TD.…”
Section: Introductionmentioning
confidence: 99%
“…There are, however, other aspects that adversely affect TD. These include technological barriers (poor internet connection, limited access to platforms, poor image quality) or lack of technological skills among professionals and patients, which could hinder attention to geriatric patients or those with a different language, ultimately resulting in the making of possibly erroneous diagnoses [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 Dermatology-related smartphone applications ("apps") grew by over 80% from 2014-2017 and COVID 19-related policy changes have catalyzed the widespread practice of teledermatology (TD) services. [3][4][5][6][7] TD is now cited as one of the most common uses of telemedicine and is an active area of clinical investigation. [8][9][10][11] Skin imaging and image utilization are central to the functionality of many dermatology applications.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of U.S. adults who own a smartphone more than doubled from 35% in 2011 to 85% in 2021, with nearly three‐quarters also reporting having desktop or laptop computers and access to in‐home broadband service 2 . Dermatology‐related smartphone applications (“apps”) grew by over 80% from 2014–2017 and COVID 19‐related policy changes have catalyzed the widespread practice of teledermatology (TD) services 3–7 . TD is now cited as one of the most common uses of telemedicine and is an active area of clinical investigation 8–11 …”
Section: Introductionmentioning
confidence: 99%
“…Although many economic assessments have been made [ 20 ], and many studies have been conducted on health results [ 18 , 19 , 21 , 22 ], many of them concluded that patients and dermatologists preferred face-to-face examinations. Additionally, no studies were found that delved into the experiences of individuals with the care received through TD.…”
Section: Introductionmentioning
confidence: 99%